GAMBARAN AKTIVITAS FISIK DAN KEBUGARAN JASMANI MAHASISWI DI KABUPATEN PURWAKARTA - Akbar, Ali; Haryanto, Irwan; Herutomo, Tomi; Lisnawati, Naintina (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2019)
Background: Physical fitness has an important roles for college students, especially for support the learning achievement, work on assignments, learning practices and organizational activities. The impact of lack of physical fitness can decrease the level of concentration of students and it can reduce learning achievement. The purpose of this study was to determine the description of physical activity and physical fitness in female college students in Purwakarta Regency. Method: This study was an analytic observational study used a cross sectional design. Subjects in this study were 66 female college students with major of health in Purwakarta Regency. Physical activity was measured using 1x24 hour physical activity recall and physical fitness was measured by the Harvard Step Test method. Analysis of the data used descriptive analysis, including mean, frequency and percentage. Result: Most of subjects (72.7%) had a light level of physical activity, while 43.9% and 34.8% of subjects had less and very less physical fitness levels, respectively. Subjects with light physical activity tend to have less physical fitness. Conclusion: Female health college students in Purwakarta Regency tend to have less physical activity and less physical fitness.